2020
DOI: 10.1186/s12870-020-2315-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide survey of the bHLH super gene family in Brassica napus

Abstract: Background: The basic helix-loop-helix (bHLH) gene family is one of the largest transcription factor families in plants and is functionally characterized in diverse species. However, less is known about its functions in the economically important allopolyploid oil crop, Brassica napus. Results: We identified 602 potential bHLHs in the B. napus genome (BnabHLHs) and categorized them into 35 subfamilies, including seven newly separated subfamilies, based on phylogeny, protein structure, and exon-intron organizat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 86 publications
2
19
0
Order By: Relevance
“…Except for HvbHLH55 , other HvbHLHs displayed the negative gravity values, representing the hydrophilic characteristics of barley bHLH genes. Subcellular location prediction showed that most (90.07%) of the HvbHLHs were localized in the nucleus, which was similar to the previous study on Brassica napus [ 11 ]. To further validate the existence of these HvbHLHs , we performed BLAST search against the barley ESTs.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Except for HvbHLH55 , other HvbHLHs displayed the negative gravity values, representing the hydrophilic characteristics of barley bHLH genes. Subcellular location prediction showed that most (90.07%) of the HvbHLHs were localized in the nucleus, which was similar to the previous study on Brassica napus [ 11 ]. To further validate the existence of these HvbHLHs , we performed BLAST search against the barley ESTs.…”
Section: Resultssupporting
confidence: 87%
“…Up to now, the bHLH gene family has been extensively identified in many plant species. It is reported that 167 bHLH genes were identified in Arabidopsis thaliana [ 2 ], 167 in rice ( Oryza sativa) [ 7 ], 146 in Brachypodium distachyon [ 8 ], 571 in wheat ( Triticum aestivum ) [ 9 ], 208 in maize ( Zea mays ) [ 10 ] and 602 in Brassica napus [ 11 ]. The bHLH genes are widely involved in diverse signal transductions and metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…A group of transcription factors contains a highly conserved amino acid motif known as basic helix-loop-helix (bHLH) domain. These bHLH proteins perform a myriad of regulatory function in eukaryotic lineages and have been studied in several plants [ 6 , 11 ]. The bHLH transcription factors have been previously studied in several plant species, including maize and potato [ 3 , 4 , 11 , 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression patterns during different growth stages and conditions could also be an indicator of gene function [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation